Investigation of the availability of biodegradable polymers in Malaysia and its impact to environment issues in Malaysia - Ng, Jia Xuan (2022)
Biodegradable polymers are created and highly recommended as the replacement to the non-biodegradable polymers to reduce the burden to the environment. In this project, two types of biodegradable polymers which are polylactic acid (PLA) and polyvinyl alcohol (PVA) have been selected to conduct in this project. To investigate the availability of the PLA and PVA in Malaysia, the environmental impacts to produce these biodegradable polymers in Malaysia have been analysed through the life cycle assessment (LCA). The production method adapted for PLA, the raw material used is DL-lactic acid, which is produced through the chemical synthesis. Then, the production method adapted for PVA, the raw material used is ethylene, which is easy to access in Malaysia. The LCA for 1 ton of PLA and PVA was conducted in the cradle-to-gate manner through a software named OpenLCA. The databases used in this project were taken from Ecoinvent 3.8 that is accessible through OpenLCA, and the ReCiPe (H) 2016 is the method used to analyse the environmental impacts generated from the production of PLA and PVA. The net consequences of the environmental impact to produce 1 ton of PLA in Malaysia was 5.52E+04 which is harmful to the environment due to the chemical synthesis used for the production of its raw material, lactic acid. The endpoint impact is the damage of human health from the water consumption affected by Tin Octoate. Then, the net consequences of the environmental impact for the PVA in Malaysia was -4.18E+08 which is friendly to the environment due to the activated carbon-supported catalyst used in the production process, the Palladium (II) Chloride. The endpoint impact is good for the human health from the global warming reduction that affected by Palladium (II) Chloride. Therefore, the availability of the PVA is better and more suitable to produce in Malaysia compared to the PLA.